Enhanced Cancer Cell (HeLa) Killing Efficacy of Mixed Î‘lpha and Gamma Iron Oxide Superparamagnetic Nanoparticles under Combined AC (Alternating Current) Magnetic-Field and Photoexcitation - and Yuji Horie, Md. Shariful Islam, Yoshihumi Kusumoto, Md. Abdulla Al-Mamun (IIUM Engineering Journal, 2011)
We synthesized mixed α and γ-Fe2O3 nanoparticles and investigated their toxic effects against HeLa cells under induced AC (alternating current) magnetic-fields and photoexcited conditions at room temperature. The findings revealed that the cell-killing percentage was increased with increasing dose for all types of treatments. Finally, 99% cancer cells were destructed at 1.2 mL dose when exposed to combined AC magnetic-field and photoexcited conditions (T3) whereas 89 and 83 % of HeLa cells were killed under only AC magnetic-field induced (T1) or only photoexcited (T2) condition at the same dose. ABSTRAK: Campuran α dan zarah γ-Fe2O3 bersaiz nano disintesiskan dan kesan toksidnya terhadap sel HeLa dikaji dibawah aruhan medan magnet arus ulang-alik (alternating current (AC)) dan keadaan photoexcited (proses ransangan atom atau molekul suatu bahan dengan penyerapan tenaga sinaran) pada suhu bilik. Penemuan mendedahkan bahawa peratusan sel yang musnah bertambah dengan pertambahan dos untuk semua jenis rawatan. Akhirnya, 99% sel kanser dimusnahkan pada kadar dos 1.2mL setelah didedahkan terhadap kombinasi medan magnet AC dan keadaan photoexcited (T3) dimana 89% dan 83% sel HeLa dimusnahkan dengan hanya di bawah aruhan medan magnet AC (T1) atau hanya pada keadaan photoexcited (T2) pada kadar dos yang sama. KEY WORDS : Cancer, Hyperthermia, Iron oxide nanoparticles, Heat dissipation, Cytotoxicity, HeLa cell.